2015
DOI: 10.1097/pas.0000000000000520
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Immunohistochemistry for 2SC and FH Aid in Detection of Fumarate Hydratase Gene Aberrations in Uterine Leiomyomas From Young Patients

Abstract: Hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome is an autosomal dominant syndrome that results from mutations in the fumarate hydratase (FH) gene. Patients with HLRCC are at risk for smooth muscle tumors of the uterus and skin as well as renal tumors. The renal cell carcinomas associated with HLRCC are usually high stage at presentation, aggressive, and have poor clinical outcomes. Therefore these patients and family members would benefit from early identification and appropriate surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
96
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 17 publications
11
96
0
1
Order By: Relevance
“…Their findings are quite similar to the nuclear features we identified in type I ALM. Joseph et al reported similar findings in their study that evaluated ALM with fumarate hydratase gene aberrations (13). They identified five cases with fumarate hydratase mutations.…”
Section: Discussionsupporting
confidence: 58%
“…Their findings are quite similar to the nuclear features we identified in type I ALM. Joseph et al reported similar findings in their study that evaluated ALM with fumarate hydratase gene aberrations (13). They identified five cases with fumarate hydratase mutations.…”
Section: Discussionsupporting
confidence: 58%
“…Some of these features have been reported in previous studies on HLRCC syndrome-associated or in some cases, FH-deficient sporadic uterine leiomyomas. 5-7 However, when comparing with non FH-deficient leiomyomas we observed similar features in non-FH-deficient atypical leiomyomas so that none of these features seem to be specific. Especially, prominent eosinophilic nucleoli, sometimes with perinucleolar halo-like clearing occurred in both FH-deficient and non-deficient leiomyomas, so that this feature is not specific for FH-deficiency.…”
Section: Discussionmentioning
confidence: 60%
“…9-11 Recently, antibodies to FH have become available opening a practical way to detect this abnormality. 7 8,12 . This is analogous to detection of succinate dehydrogenase deficiency in certain tumors, especially subsets of paragangliomas, gastrointestinal stromal tumors, and renal cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations